Booking Curves as an Instrument of Increasing of Independent Hotel Enterprise Efficiency. Case of Russia - POPOV, Leonid A.; ROMANYUK, Anton V.; BLINOVA, Ekaterina A.; GAREEV, Roman R. (Journal of Environmental Management and Tourism; Vol 8 No 6 (2017): JEMT Volum VIII Issue 6(22) Fall 2017, 2018)
The article deals with the use of such a method of revenue management as the use of booking curves. Based on the results of a study conducted by LLC Hotel Business Consulting jointly with hotel companies in Moscow, a great number of three-star hotels and those with more number of stars do not fully use existing methods of revenue management which affects the effectiveness of their activities. It was concluded that the three-star hotels in Moscow do not have a Revenue Manager as a position in the company's staff. Partial functionality in the sphere of Revenue Management is performed by employees from other departments such as Front Office, Sales and others. In this article, we give an example of the calculation of typical booking curves for three-star hotels, taking into account seasonality and typical segments. With the help of these typical booking curves, hotel companies will be able to function more efficiently.